The Effectiveness of the Service for Issuing Certificates of Residence at the Benda Village Office - Apriliandani, Nur Afni; Hidayat, Moh. Taufik (Journal Of Social Science (JoSS), 2026)
This study examines the effectiveness of public service delivery in issuing Certificates of Residence at the Benda Village Office, Karangampel Subdistrict, Indramayu Regency. Public service effectiveness is crucial in ensuring administrative efficiency, community satisfaction, and good governance at the village level. The objective of this research is to analyze the level of service effectiveness and identify supporting and inhibiting factors in the issuance process. This study employed a qualitative approach with a case study design. Data were collected through observations, in-depth interviews, documentation, and literature review, involving village officials and community members as informants selected through purposive sampling. The analysis is based on Agus Dwiyanto’s framework of public service effectiveness, which includes productivity, service quality, responsiveness, responsibility, and accountability. The findings indicate that overall service effectiveness is categorized as fairly good. Service quality, responsiveness, and responsibility have been implemented effectively, reflected in accurate documentation, responsive communication, and adherence to procedures. However, productivity and accountability still face challenges, particularly due to limited internal coordination and the absence of formal feedback mechanisms. These constraints lead to occasional service delays and limited public participation in evaluation processes. In conclusion, while the service for issuing Certificates of Residence at the Benda Village Office is generally effective, continuous improvements are needed, especially in strengthening coordination and enhancing transparency and community involvement to achieve optimal public service delivery